Remediation of sulfidic wastewater by catalytic oxidation with hydrogen peroxide - N., Ahmad (2009)
Oxidation of sulfide in aqueous solution by hydrogen peroxide was investigated in the presence of hydrated ferric oxide catalyst. The ferric oxide catalyst was synthesized by sol gel technique from ferric chloride and ammonia. The synthesized catalyst was characterized by Fourier transform infrared spectroscopy, X-Ray diffraction analysis, scanning electrom microscope and energy dispersive X-ray analysis. The catalyst was quite effective in oxidizing the sulfide by hydrogen peroxide. The effects of sulfide concentration, catalyst loading, H2O2 dosing and temperature on the kinetics of sulfide oxidation were investigated. Kinetic equations and activation energies for the catalytic oxidation reaction were calculated based on the experimental results. © 2009 The Research Centre for Eco-Environmental Sciences, Chinese Academy of Sciences.